El juego experimental como estrategia para mejorar el aprendizaje del ámbito de relaciones con el medio natural y cultural de los niños de 4 a 5 años de la unidad educativa fiscomisional la inmaculada de la ciudad de Loja, periodo académico 2018 - 2019. - Valdivieso Luzuriaga, Cinthya Maria (2020)
The present research work entitled THE EXPERIMENTAL GAME AS A STRATEGY TO IMPROVE THE LEARNING OF THE RELATIONSHIP WITH THE NATURAL AND CULTURAL ENVIRONMENT OF CHILDREN FROM 4 TO 5 YEARS OF THE IMMACULATE EDUCATIONAL UNIT THE IMMACULATE OF THE CITY OF LOJA, ACADEMIC PERIOD 2018 - 2019, whose purpose is to determine the experimental game as a strategy to improve learning in the area of relations with the natural and cultural environment. To carry out the study, the following methods were used: scientific, analytical-synthetic, descriptive, statistical and comparative. The instruments used to collect information were: an interview with the teacher and an assessment scale, whose criteria were taken from the Ministry of Education’s Early Childhood Curriculum, which made it possible to diagnose that the vast majority of children were in the process pf acquiring the skills. The most relevant results showed than in conversation of the environment and recognizing healthy and unhealthy food all children were at the beginning of acquiring the skill. After applying the proposed activities, the progress was made so that a large number of children are in the process and others in the process of acquiring them. Therefore, it is concluded that experimental play as a strategy for learning about the natural and cultural environment is a useful tool in the teaching process since, through the experiences that the children lived, they learned to protect the environment in which they develop and improved their eating practices, especially in the school context.